Complete Genome Sequence of a Polyomavirus Isolated from Horses - Renshaw, Randall W. (American Society for Microbiology, 2012)
A polyomavirus was isolated from the eyes of horses, and the sequence was determined. A nearly identical VP1 sequence was amplified from the kidney of another animal. We report the complete genome sequence of the first polyomavirus to be isolated from a horse. Analysis shows it to be most closely related overall to human and nonhuman primate polyomaviruses.